Neglect of Growing Income and Asset Inequalities: A Flaw in Public Policy Discourses in India. Issue 2 (August 2018) - Shetty, S. L.
The article seeks to flag a fundamental flaw in public policies in India, namely, the neglect of growing inequalities in income and asset distributions and their causes and consequences. The article sets out a series of direct and indirect indicators of income and asset inequalities: inter-sectoral inequalities between rural-urban and farm and non-farm incomes, inter-state inequalities, gross inequalities in the distributions of urban incomes as per income-tax revenue statistics and explosive increases in remunerations of company executives. It has been pointed out that both in conception and actual implementation of the "inclusive growth" strategy, serious compromises have been made and inequalities have got worsened. In this respect, the article quotes extensively a comprehensive study done by the World Economic Forum very recently, which points out how India scores very poorly in its Inclusive Development Index (IDI) and attributes it to various policy failures.